Rosai–Dorfman Disease of the Central Nervous System with a Rare Presentation as an Arachnoid Cyst - Sunayana Misra; Shashi Dhawan; Seema Rao (CHRISMED Journal of Health and Research)
Rosai–Dorfman disease (RDD) is an uncommon histiocytic disorder presenting with painless massive lymphadenopathy. Extranodal RDD is seen in up to 30% of cases and commonly involves the skin and bone. Central nervous system (CNS) involvement by RDD is very rare, occurring in <5% of cases. In the CNS, RDD is usually seen as dural-based lesion mimicking meningiomas or as intraparenchymal solid lesions. The presentation of RDD in a posterior fossa arachnoid cyst has not been previously reported. To the best of our knowledge, we report the first case of isolated extranodal RDD in the CNS presenting in the wall of a retrocerebellar arachnoid cyst.